Pengaruh Promosi, Harga dan Kualitas Pelayanan Terhadap Kepuasan Konsumen pada PT Happy Kiddy Indonesia Rantauprapat - Heni Aulia Safitri; Rizky Syahputra; M Ali Al Ikhsan (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
The purpose of this study was to determine the effect of promotion, price and service quality on consumer satisfaction at PT Happy Kiddy Indonesia Rantauprapat. The sample used was 100 people, namely Happy Kiddy Rantauprapat consumers. The results of the study showed that promotion, price and service quality had a positive and significant effect both partially and simultaneously on consumer satisfaction. For the promotion variable, the t-count value was obtained (3.664) > t table (1.661) with a significance level of 0.000 <0.05. This means that promotion has a positive and significant effect on consumer satisfaction. For the price variable, the t-count value was obtained (2.980) > t table (1.661) with a significance level of 0.001 <0.05. This means that price has a positive and significant effect on consumer satisfaction. For the service quality variable, the t-count value was obtained (5.874) > t table (1.661) with a significance level of 0.000 <0.05. This means that service quality has a positive and significant effect on consumer satisfaction.